The first observation of Ni nanoparticle exsolution from YSZ and its application for dry reforming of methane - Sangwook Joo; Chaehyun Lim; Ohhun Kwon; Linjuan Zhang; Jing Zhou; Jian-Qiang Wang; Hu Young Jeong; Yong-wook Sin; Sihyuk Choi; Guntae Kim (Materials Reports: Energy, 2021)
Ni nanocatalysts produced through exsolution have shown strong resistance to particle sintering and carbon coking in a beneficial dry reforming of methane (DRM) reaction utilizing greenhouse gases such as CH4 and CO2. However, most of the existing oxide supports for exsolution have been limited to perovskite oxide, while studies on fluorite support have been rarely conducted due to the limited solubility despite its excellent redox stability. Here we demonstrate that 3 ​mol% Ni can be successfully dissolved into the yttria-stabilized zirconia (YSZ) lattice and be further exsolved to the surface in a reducing atmosphere. The YSZ decorated with exsolved Ni nanoparticles shows enhanced catalytic activity for DRM reaction compared to the conventional cermet type of bulk Ni-YSZ. Moreover, the catalytic activity is extremely stable for about 300 ​h without significant degradation. Overall results suggest that the YSZ-based fluorite structure can be utilized as one of the support oxides for exsolution.